Time trends in physical activity in the Tromsø study: An update - Morseth, Bente; Hopstock, Laila Arnesdatter (PLOS ONE, 2020)
Although the health benefits of physical activity are well documented, a large proportion of the population fails to meet current guidelines for physical activity. In order to develop evidence-based public health policies, surveillance of physical activity prevalence and trends is essential. The main aim of this study was to present updated data on physical activity trends in a Norwegian general population over the last decades. Data were collected from 40 690 individuals (50% men) aged ≥20 years participating in at least one of six surveys of the population-based Tromsø Study between 1979 and 2016. Age-standardized prevalences and trends in leisure-time and occupational physical activity were obtained from three questionnaires used in the different surveys. We observed an increase in the proportion engaging in exercise in leisure-time between 1994–95 and 2001 ( p <0.001). Based on a different questionnaire, the age-standardized prevalence of engagement in exercise in leisure-time increased significantly from 16% in 2001 to 23% in 2007–08, and further to 28% in 2015–16 ( p <0.001). The proportion who reported exercising approximately every day increased from 19% in 2007–08 to 28% in 2015–16 ( p <0.001). The age-standardized prevalence of sedentary occupational activity increased from 53% in 2007–08 to 57% in 2015–16 ( p <0.001), which extends the gradual increase from 36% in 1979-80.The present study extends previous findings from the Tromsø Study by demonstrating an increase in the proportion exercising regularly over the last three decades. This increase may partially counteract the gradual increase in the proportion with sedentary occupational activity.